2021
DOI: 10.22159/ijpps.2021v13i8.42643
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanoparticles: An Alternative Therapy to Combat Drug Resistant Infections

Abstract: One of the most urgent challenges that medical sciences face today is overcoming the problem of drug resistance. This review paper encompasses research studies that provide a solution towards this major concern. It aims to highlight the therapeutic effects of various metal-based nanoparticles over conventional antibiotics. Severe infections caused by bacteria, viruses, fungi and parasites are transmitted easily and spread across millions of people round the globe. Resistance developed by these organisms and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 179 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…β-Cyclodextrin (β-CD; polymer) based NSs were prepared in our laboratory by using diphenyl carbonate as a cross-linking by ultrasoundassisted method for fabrication of Entrectinib. β-CD was dissolved in dimethyl formamide, to which diaryl carbonate was added and was left for completion of the reaction and formation of NSs [13].…”
Section: Preparation Of Entrectinib Nssmentioning
confidence: 99%
“…β-Cyclodextrin (β-CD; polymer) based NSs were prepared in our laboratory by using diphenyl carbonate as a cross-linking by ultrasoundassisted method for fabrication of Entrectinib. β-CD was dissolved in dimethyl formamide, to which diaryl carbonate was added and was left for completion of the reaction and formation of NSs [13].…”
Section: Preparation Of Entrectinib Nssmentioning
confidence: 99%
“…NBDDS have sparked a lot of research interest in recent years because of the potential benefits, such as improving lipophilic drug solubility, increasing permeability, improving drug stability, controlling drug distribution and elimination, and targeting drug delivery to a specific site. Several NBDDS have been produced, including nanocrystals, nanoemulsions, nanosponges (NSs), nanobubbles, liposomes, polymeric micelles, polymeric nanoparticles, and inorganic nanocarriers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous NBDDS have been produced, including nanocrystals, nanoemulsions, nanosponges (NSs), nanobubbles, liposomes, micelles, nanoparticles, & inorganic nanocarriers. 7,8 Many studies have shown that NS dosage forms can amplify solubility and thus oral availability of weakly soluble medicines. 9 They shield molecular compounds from degradation and these have high selectivity, biocompatibility, degradability, and extended release behavior which are used in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%